Parametric Processes for the Implementation of HBIM—Visual Programming Language for the Digitisation of the Index of Masonry Quality - Calvano, Michele; Martinelli, Letizia; Calcerano, Filippo; Gigliarelli, Elena (ISPRS international journal of geo-information, 2022)
The heterogeneity and historical complexity of interventions on built heritage are testified by the constant development of the conservation discipline. The purpose of the research is the development of a digital workflow of parametric modelling for the analysis and conservation of historical buildings, by applying visual programming language (VPL) to support the Heritage Building Information Modelling (HBIM) methodology. VPL represents a tool for explicit parametric modelling that can be used to enhance geometric and information enrichment of HBIM models. The paper describes the integration, within an HBIM-VPL process, of the Index of Masonry Quality, widely used for seismic structural analysis, and its application to a case study in Cornillo Nuovo, a village damaged by the earthquake of Amatrice in 2016. Similar approaches could enhance HBIM modelling to support different knowledge domains associated with built heritage.